Association of Laparoscopic Methods and Clinical Outcomes of Cholecystolithiasis Plus Choledocholithiasis: A Cohort Study - Ji, Hui; Hou, Yafeng; Cheng, Xiaojian; Zhu, Feng; Wan, Chao; Fang, Lei (Turkish Journal of Gastroenterology, 2022)
Background: Various surgical methods are available for cholecystolithiasis plus choledocholithiasis. The objective of this study is to explore the association between laparoscopic methods and clinical outcomes of cholecystolithiasis plus choledocholithiasis. Methods: This cohort study retrospectively included patients who underwent laparoscopic surgery for cholecystolithiasis plus choledocholithiasis at our hospital (January 2017 to March 2021). The primary outcome was bile leakage. Results: Totally 127 patients were enrolled. The time to get out of bed and the indwelling duration of the abdominal drainage tube in the patients who underwent laparoscopic cholecystectomy+lithotomy of common bile duct+common bile duct primary suture+endoscopic nasobiliary drainage were higher than the endoscopic retrograde cholangiopancreatography+laparoscopic cholecystectomy group, without differences in the laparoscopic common bile duct exploration group (all P < .05). All indexes decreased in the 3 groups after surgery (all P < .01). On the first day after surgery, only white blood cells (P < .001) and gamma-glutamyl transferase (P = .045) showed significant differences among the different surgical methods. The incidence of biliary leakage (P = .001) was higher in laparoscopic cholecystectomy+lithotomy of common bile duct+common bile duct primary suture+endoscopic nasobiliary drainage, while the occurrence of hyperamylasemia was higher with endoscopic retrograde cholangiopancreatography+laparoscopic cholecystectomy (P = .001). Compared with laparoscopic cholecystectomy+lithotomy of common bile duct+common bile duct primary suture+endoscopic nasobiliary drainage, laparoscopic common bile duct exploration was associated with fewer bile leakage (RR = 0.03, 95% CI: 0.003-0.37). Conclusion: Compared with laparoscopic cholecystectomy+lithotomy of common bile duct+common bile duct primary suture+endoscopic nasobiliary drainage, laparoscopic common bile duct exploration was associated with bile leakage. Cite this article as: Ji H, Hou Y, Cheng X, Zhu F, Wan C, Fang L. Association of laparoscopic methods and clinical outcomes of cholecystolithiasis plus choledocholithiasis: A cohort study. Turk J Gastroenterol. 2023; 34(1): 35-42.